Inspirational Leadership and Innovative Communication in Sustainable Organizations: A Mediating Role of Mutual Trust - Toseef, Muhammad; Kiran, Alina; Zhuo, Sufan; Jahangir, Mahad; Riaz, Sidra; Wei, Zong; Ghauri, Tauqir Ahmad; Ullah, Irfan; Ahmad, Suraya Binti (Frontiers in Psychology, 2022)
The possibility of accomplishing sustainable objectives largely connected to the management and flourishing organizational system which keeps human capital engage and committed. Our study investigated the association of inspirational leadership and innovative communication with to employee engagement and commitment under the lens of LMX theory. Specifically, emphasized on the mediating role of mutual trust in connection to social sustainability facets. A survey of data from employees in the manufacturing sector of Yunnan, China was utilized to test hypothesized model. The study findings reported significant association and came with a conclusion that leader’s inspirational behavior coupled with innovative communication are significant predictor of engagement and commitment in socially sustainable organizations. Moreover, mutual trust significantly mediated the relationship of innovative communication and inspirational leadership with employee engagement and commitment reaching social perspective of sustainability. The current study added to the literature of sustainable organization by pointing social dimensions of sustainability.